BUSINESS FEASIBILITY STUDY OF FRUZFRUIT SORBETTO - Supriyatin, Yulinda; Sonny, Sonny (President University, 2024)
Following the pandemic that affected practically everyone in the world, includingIndonesia, the government recommended that people consume fruits more attentively asa self-protection strategy against the coronavirus. This is a healthy trend that mustcontinue to improve Indonesian nutrition. As a result, the author decided to launchFruzfruit Sorbetto, a frozen dessert sorbet business based on high-quality fresh fruits andmade from fruit raw materials, thus it has a considerably higher nutritional value and ishealthier. The goal is to give an alternate method to enjoy fruit. The Fruzfruit Sorbettocompany is expected to have a payback in year three and a total net present value (NPV)purchase of Rp. 218.265.256 in year five, with a sales ratio of 34%. Thus, FruzfruitSorbetto will constantly prioritize continual innovation and deliver the greatest serviceto provide a positive experience for every consumer.Keywords: Sorbet, fruit, business feasibility, business plan, healthy frozen dessert.